Inclusiveness of the Concept of Mental Disorder and Differences in Help-Seeking Between Asian and White Americans - Tse, Jesse S. Y.; Haslam, Nick (Frontiers in Psychology, 2021)
Ethnic and racial group differences in help-seeking are a barrier to the effective and equitable delivery of mental health services. Asian American populations demonstrate relatively low levels of help-seeking. Explanations for this effect typically point to elevated levels of stigma in these populations. An alternative explanation is that low help-seeking might also reflect holding a relatively circumscribed concept of mental disorder. Individuals and groups with less inclusive concepts of disorder may be less likely to identify problems as appropriate for mental health treatment. This study aimed to test whether group differences in the breadth of the mental disorder concept account for group differences in help-seeking attitudes. A sample of 212 American participants (102 Asian Americans, 110 White Americans) were assessed on personal stigma, help-seeking attitudes, and mental disorder concept breadth. Mediation analyses examined whether stigma and concept breadth mediated group differences in attitudes. Compared to White Americans, Asian Americans reported higher levels of stigma and narrower concepts of mental disorder, both of which were associated with less positive help-seeking attitudes. Stigma and concept breadth both partially mediated the group difference in attitudes. Theoretical and practical implications for mental health promotion and culturally sensitive clinical practices are explored.